STRES AKADEMIK SISWA SMA N 1 PASIR PENYU SELAMA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The Covid-19 pandemic has caused the government through the Minister of Education and Culture of the Republic of Indonesia to issue circular number 4 of 2020 concerning the Implementation of Education Policies in an Emergency for the Spread of COVID-19. Thus, learning that was previously carried out face-to-face turns into learning that is done online or via an internet connection. The rapid change in the learning system from face to face to an online system causes students to experience academic stress caused by various obstacles and constraints such as unstable internet connection, difficulty understanding material, task load, limited internet quota, and so on. Therefore, this study aims to determine the level of academic stress of students at SMAN 1 Pasir Penyu during online learning during the Covid-19 pandemic. This study used a survey approach with a sample of 155 students. The data was collected using a Likert-type scale which has been tested for validity and reliability, and was analyzed by using the percentage technique. Based on the data analysis, it was found that the average student at SMAN 1 Pasir Penyu experienced academic stress in the high category. The results showed that the highest academic stress experienced by grade X students, while the academic stress aspect most experienced by students at SMA N 1 Pasir Penyu was the intellectual aspect.Key Words: Stress, Student Academic, Online